X-ray-induced mutation of Bacillus sp. MR10 for manno-oligosaccharides production from copra meal - Siriporn Chaikaew (2018)
© 2017 Taylor & Francis. The present study demonstrates the effectiveness of X-ray radiation in strain improvement for defective lipase production by Bacillus sp. MR10 for further application in the fermentative production of manno-oligosaccharides (MOS) from agricultural by-product, defatted copra meal (DCM). The mutants obtained were screened based on their defective lipase activity together with their β-mannanase production performance. Among 10 selected mutants, the strain M7 was the highest promising mutant regarding the smallest lipase activity (0.05 U/ml) and the retained β-mannanase activity similar to the parental strain (22 U/ml) were detected. The mutant M7 effectively hydrolyzed DCM to MOS with low-degree of polymerization (DP) oligomers including mannotriose (M3), mannotetraose (M4), and mannopentose (M5) as the main products. Although the pattern of DCM hydrolysis products of mutant M7 was distinctly different from wild type, the biochemical and catalytic properties of purified β-mannanase of mutant were similar to those of wild type. Both purified β-mannanases with apparent molecular mass of 38 kDa displayed optimal activity at pH 5–7 and 45–55°C. Co2+and Hg2+nearly completely inhibited activities of both enzymes, whereas Ba2+, Fe3+, and 2-mercaptoethanol obviously activated enzyme activities. Both enzymes showed high specificity for locust bean gum, konjac mannan, DCM, and guar gum. Thus, the mutant M7 has a potential for commercial production of high-quality MOS from low-cost DCM for further application in the feed industry.